Data Security Through Armstrong Number and Colors - John, Ajisha; Keerthy, KB; Manoharan, Meenu; Davis, Diana (International Journal of Computer Sciences and Engineering, 2014)
Data Security is the science and study of methods of protecting data from unauthorized disclosure and modification. As the technology advanced, there is need to secure data, transmitted over the network. To make secure data transmission, different methods are used. One of the techniques is Cryptography. Cryptography is the universal technique for secure data communication with the presence of third parties. In this method, encryption and decryption process is used to hide simple data from unauthorized users by converting it into unreadable form and again retrieve it in original form. This method not only protect data from theft, but also used for user authentication. Encryption and decryption have need of some secret information, called key.